STUDI PEMANFAATAN TANAMAN PADA KEGIATAN RITUAL (UPAKARA) OLEH UMAT HINDU DI BALI - Sardiana, I Ketut; Dinata, I Ketut Kartha (Bumi Lestari; Vol 10 No 1 (2010), 2010)
Ritual is one of basic element on Baliâ€™s Hindu society. Most of the ritual elements are descended from plants which are well known as â€œritual plantsâ€. The objective of the present studies are to study plants utilization in Baliâ€™s Hindu ritual activity. The research was conducted through field survey and literature studies, on several villages in Bali in which classified as Bali Age village, Bali Apanege village and new Bali village. The findings showed that utilization of plants in Baliâ€™s Hindu rituals as an actualization of tri hita karana concept, especially in developing harmonization between human and their environment relationships. Approximately two hundred kind of plants which commonly used on Bali Hindu rituals. The plants can be classified within several groups such as : kind of coconuts, bamboos, trees, leaves, flowers, bananas, fruits (pala gantung), yam group (pala bungkah), etc. Now day, many kind of the plants are entirely disappeared, it need a real action program on ritual plants preservation in other to preserve the ritual plants.
Keywords: utilization; plants; rituals; preservation